(untitled) (The Pretoria Student Law Review, 2023)
Sport undeniably plays a major role in society today. Over the years, ithas developed into n free-standing industry and its players have becomeincreasingly valuable and earn income both on and off the field. Thisarticle addresses the income generated by sport stars off the field ofplay through the exploitation of their ‘image rights’. The use ofsomeone’s image rights can be explained as the practice ofappropriating someone’s personality. In modern society, people havebecome transfixed by sport stars. This has led to the image rights ofindividual sport stars such as Lionel Messi and Cristiano Ronaldo tobecome commodities exploited by their clubs and other third parties toenhance brand images and promote the sale of products.1 This use ofthe image rights of celebrities generates a whole new source of incomefor these sport stars. Due to the relatively high amounts of incomereceived for the use of a sport star’s image, these stars may be temptedto enter into creative schemes in an attempt to reduce high taxes leviedagainst these streams of income. The practice of the commercialexploitation of a sport star’s image rights is a relatively new development in South Africa and is not yet recognised to the same extent as in other jurisdictions, such as the UK and Spain. This article examines the existing South African sport, intellectual property, andtax laws governing image rights and specifically analyses whether SouthAfrica is sufficiently equipped, under tax legislation, to address theseminimisation schemes aimed at reducing the tax liability arising from aSouth African sport star’s image rights.